"America's Theologian" Enters the Middle Kingdom: Uncovering the Earliest Chinese Reception of Jonathan Edwards - Pino, Ryan (Jonathan Edwards studies, 2019)
While in the library at Yale Divinity School collecting materials for a graduate thesis on a nineteenth-century Chinese Christian pastor, I was perusing a 1907 review of Protestant evangelistic labors titled A Century of Protestant Missions in China.